A morte na poética neolatina setecentista: os gêneros retórico-poéticos e sua recepção nos epigramas fúnebres de relação panegyrica - Silva, Ruth dos Santos (2023)
The present dissertation aims at analyzing twelve neo-latin epigrams of Relação Panegyrica das honras funeraes, às memórias do muito alto, e muito poderoso senhor Rey fidelissimo D. João V , Consagrou a Cidade da Bahia Corte da America Portugueza: escrita, e dedicada ao excellentissimo, e Reverendissimo senhor D. Joseph Botelho de Mattos, Arcebispo da Bahia, primaz dos Estados do Brasil, do Conselho de Sua Magestade, published in 1753, and organized by João Borges de Barros, identifying which elements of the epideictic and epigrammatic genres were received from classical Antiquity. The Relação Panegyrica is a funeral and multilingual text of praise produced in Portuguese America. Initially, we discuss the dynamic between the Latin and vernacular languages in the Early Modern Period considering Europe and also the other territories around the globe, as well as the social-political context of Portugal and the Luso-Brazilian lands during the government of D. João V and the Neo-Latin literate practices of the 18th century. Then, we argue about the reception of epideictic and epigrammatic genres considering the precepts of Antiquity and the reformulation of their topics within the modern poetical precepts. For the discussion about what was understood as poetry in the Early Modern Era, we used the manuals of modern poetics by Freire (1759), Luzan (1737), Vossio (1647), and Grácian (1725). And finally, we discuss the relações as a genre as well as the concept of death in the 18th century and its relation with epideictic rhetoric. We also analyzed the reception of epigrammatic categories in selected poems from Relação Panegyrica such as hyperbole, ekphrasis and metaphor. The research concludes that the reception of texts and rhetorical devices from classical antiquity is not only an imitation, but also a rhetorical performance that demonstrates which approximations and distances are made between the ancient material and the modern poetic matter. Furthermore, we realized that these elements are used both for the praise of D. João V and also to help build a virtuous image of the king and for the narrative effect of the monarch's funeral. In the appendices, we present the full translation of the Latin epigrams.